Major trends in the historiography of Muslim reformism in pre-Independent Malaysia - Zakariya, Hafiz (IIUM Press, 2019)
Muslim reformism, which emerged in West Asia during the closing years of the nineteenth century, and the early twentieth, was spearheaded by Jamal al-Din al-Afghani and Muhammad ‘Abduh. It responded to the socio-economic and political challenges confronting the Muslim society. Muslim reformism was not only influential in West Asia but also in Southeast Asia. However, most studies on Muslim reform have privileged the “central Islamic lands” at the expense of its “periphery”. As a result, Muslim reform in Malaysia has been marginalised. Thus, this article, discusses the historiography of Muslim reform in Malaya. An analysis of the major writings in English and Malay identified the major trends, issues, and gaps. It argues that the existing studies tend to focus on the intellectual history of reform, while the social history of the diffusion of reformism has not been adequately analysed. Similarly, most works on reform in Malaysia focus on its development in the country alone without embarking upon comparative analysis with other areas such as West Sumatra, Aceh and Java. Existing biographies of reformists focusing on prominent figures such as Syed Sheikh al-Hadi and Sheikh Tahir have been thoroughly examined while other reformists such as Abu Bakar Ashaari, Abdullah Maghribi, and Abu Bakar Bakir have not been adequately studied.